2010
DOI: 10.3171/2010.7.focus10170
|View full text |Cite
|
Sign up to set email alerts
|

A systematic analysis of disease control in acromegaly treated with radiosurgery

Abstract: Object Stereotactic radiosurgery (SRS) has emerged as an adjuvant radiation-based therapy for pituitary adenomas. Here, the authors present a systematic analysis of SRS for growth hormone–secreting adenomas to characterize the efficacy of SRS in the treatment of acromegaly. Methods A comprehensive search of the English language literature revealed 970 patients with new, recurrent, or persistent acromegal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 56 publications
1
13
2
1
Order By: Relevance
“…Surgical cure of GH-producing microadenomas is favorable, with rates of approximately 75–95%; however, on account of the insidious nature of the disease and oftentimes resultant late diagnosis, most present as macroadenomas, which are cured by surgery alone only 40–68% of the time. [89] Although surgical debulking, even in cases of subtotal resection, can lead to improved medical management,[33] patients are dependent on somatostatin analogs and GH antagonists for life, which can become very costly. Early work with fractionated radiotherapy demonstrated that radiation therapy can result in GH normalization, however, in addition to the typical side effects of pituitary deficits and cranial neuropathies, the time to remission was in the order of decades, an unfavorable delay before treatment effect, given the continued morbidity with elevated GH and IGF-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical cure of GH-producing microadenomas is favorable, with rates of approximately 75–95%; however, on account of the insidious nature of the disease and oftentimes resultant late diagnosis, most present as macroadenomas, which are cured by surgery alone only 40–68% of the time. [89] Although surgical debulking, even in cases of subtotal resection, can lead to improved medical management,[33] patients are dependent on somatostatin analogs and GH antagonists for life, which can become very costly. Early work with fractionated radiotherapy demonstrated that radiation therapy can result in GH normalization, however, in addition to the typical side effects of pituitary deficits and cranial neuropathies, the time to remission was in the order of decades, an unfavorable delay before treatment effect, given the continued morbidity with elevated GH and IGF-1.…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis by Yang et al . [89] evaluated the rates of remission based on study-specific criteria and found that following SRS the rate of cure was approximately 48–53%. Endocrine normalization improved to 60.3% when also including patients who met the criteria for cure while on hormone suppressive medications.…”
Section: Resultsmentioning
confidence: 99%
“…72 In these studies the remission rate was 45%, with a mean duration of reported follow-up of 4.6 ± 1.7 years. 72 When all of the studies were included in the analysis, an overall disease control rate of 48% was seen after SRS (without adjuvant medical therapy).…”
Section: Radiation Therapymentioning
confidence: 87%
“…There is, however, no compelling evidence to support this. Loss of pituitary function after either therapy is usually limited to 1 or 2 pituitary functions, rather than panhypopituitarism, and it occurs over several years, accumulating for 10-15 years after treatment, as summarized in the current issue in reports by Stapleton et al 8 and Yang et al 9 Because with radiosurgery we have access to very few studies with follow-up durations beyond 5 years (see the tables in the reports by Rowland et al, 7 Stapleton et al, 8 and Yang et al 9 ), the true incidence of adverse effects on pituitary function over time cannot be known until the data to measure it are available. For instance, in the only radiosurgery series with a minimum median follow-up of 10 years, 6 46% of patients with acromegaly who underwent radiosurgery had endocrine remission at 10 years and 50% developed new anterior pituitary insufficiencies, the majority of which appeared more than 5 years after treatment.…”
Section: Radiosurgery Versus Fractionated Radiation Therapymentioning
confidence: 99%